Using Microsoft PowerApps, Mendix and OutSystems in Two Development Scenarios: An Experience Report - Gurcan, Fulya; Taentzer, Gabriele (2021 ACM/IEEE International Conference on Model Driven Engineering Languages and Systems Companion (MODELS-C), 2021)
Digitalisation, rapid and low-cost development, and a new communication base between business and IT are driving the rise of low-code development platforms (LCDPs). Picking up on this promise, this paper reports on our experiences with the development capabilities of three leading LCDPs: Microsoft PowerApps, Mendix and OutSystems. We present how to develop the same example application on each of these platforms. Two relevant development scenarios are considered. The first scenario describes the development of an independent application entirely implemented on an LCDP. Whereas the second scenario focuses on developing a dependent application using an existing local backend. The results of this paper may contribute to future research on the development potentials of LCDPs and the improvement needs of existing ones.